Education law and the private schools : a practical guide for educational leaders and policymakers - Sarmiento, Ulpiano P. ([Manila, Philippines] : Ulpiano P. Sarmiento, 2009)
This book remains faithful to aim of being an indispensable companion of educational leaders as well as policymakers. Likewise, endeavors to continually be of aid to the operations of educational institutions in accordance with law and latest jurisprudence.
Chapter 1. General Provisions -- Chapter 2. The Education system -- Chapter 3. Education institutions -- Chapter 4. Terms and conditions of employment -- Chapter 5. School Finance and Assistance -- Chapter 6. Miscellaneous Provisions.
Includes index.
Keywords: EDUCATIONAL LAW AND LEGISLATION